Valorization of onion solid waste and their flavonols for assessment of cytotoxicity, enzyme inhibitory and antioxidant activities. (September 2018) - Nile, Arti; Nile, Shivraj Hariram; Kim, Doo Hwan; Keum, Young Soo; Seok, Park Gyun; Sharma, Kavita
Abstract: Onion ( Allium cepa L.) is rich with flavonols which perceived benefits to human health. Flavonols like quercetin and quercetin glycosides from onion solid waste (OSW) have been extracted and tested against enzymes of clinical importance in Alzheimer's disease and diabetes and be shown to have cytotoxic and antioxidant effects. A simple high-performance liquid chromatography-diode array detector method using a Zorbax Eclipse XDB C18 column was developed to separate quercetin-3, 4′-O-diglucoside, quercetin-4′-O-monoglucoside, and quercetin from OSW. These compounds were identified using infrared, ultra-violet, 1 H, and 13 C nuclear magnetic resonance spectroscopic techniques. The OSW solvent fractions and flavonols showed significant antioxidant activities using DPPH (1, 1-diphenyl-2-picrylhydrazyl), FRAP (ferric reducing antioxidant power), and ABTS (2, 2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid) radical scavenging assays. The samples exhibited significant in vitro anti-cholinesterase activity with strong antidiabetic effects. OSW extracted with methanol and ethanol showed greater in vitro anti-cholinesterase and hypoglycemic effects than QDG, QMG, and Q possibly due to interactions between multiple compounds and/or complex multivariate interactions with other factors in OSW. In addition, cytotoxicity assays showed that OSW and QDG, QMG, and Q could inhibit the proliferation of selected cancer cell lines. Results indicate that OSW and flavonol glycosides are potential antioxidant, antidiabetic, anticancer, and sedative agents.